Recombinant cancer nanovaccine for targeting tumor-associated macrophage and remodeling tumor microenvironment. (October 2021) - Tang, Yisi; Fan, Wufa; Chen, Guihua; Zhang, Meng; Tang, Xueping; Wang, Hairui; Zhao, Pengfei; Xu, Qin; Wu, Zhibing; Lin, Xiaoxi; Huang, Yongzhuo
Highlights: Old drug for new application: trichosanthin can serve as a cancer vaccine adjuvant for effectively stimulating anti-tumor immunity. The liposomal novel nanovaccine is characterized by an 'all-in-one' recombinant form of antigen and adjuvant. The vaccination is targeting TAMs and the selective elimination of TAMs can activate anticancer immunity and thus remodel TIME. The efficacy of this vaccine is demonstrated in various tumor models, indicating its application universality. Graphical Abstract: ga1 Abstract: The efficient cancer vaccines require the codelivery of potent antigens and highly immunostimulatory adjuvants to the same antigen-presenting cells (APCs) to initiate a robust immune response. In this work, a clinically used trichosanthin served as an adjuvant to prepare a minimalist "all-in-one" vaccine that was a recombinant protein (termed rTL) of trichosanthin and an antigen legumain peptide. rTL was further incorporated into a nanovaccine delivery system (LrTL) using a liposome-encapsulated technology. LrTL can trigger a robust cytotoxic T lymphocytes (CTL) response by activation of APCs that enhance immunostimulatory cytokine secretion (e.g., TNF-α, IL-12, and IFN-γ) and trigger T-cell immunity. By targeting tumor-associated macrophages (TAM), the nanovaccine carried out the anticancer immunity by eliminating TAM and thereby remodeling the tumor microenvironment. Subcutaneous immunization with the nanovaccine yielded a potent anti-tumor activity in several cancer models, including B16-F10, Lewis lung cancer (LLC), intracranial LLC xenograft, as well as CT-26 colon cancer. These findings demonstrate that the nanovaccine is a simple, safe, and robust strategy for cancer immunotherapy. The vaccination strategy offers a general applicability in various cancer types by targeting TAM and remodeling tumor microenvironment.